Implementation of Creative Dance Based on Sundanese Pakakas to Develop Creativity and Local Cultural Awareness in Elementary School Students - Apriani, Arni; Dharma, Budi; Ghani, Abdul; Nur, Zahra Ghaida (JUPE : Jurnal Pendidikan Mandala, 2025)
This study aims to implement creative dance based on Sundanese pakakas to develop creativity and local cultural awareness in elementary school students. Globalization and the development of digital technology have resulted in a decline in the younger generation's understanding of traditional Sundanese cultural heritage, especially pakakas (traditional household utensils). This study involved 32 students from Muhammadiyah Elementary School in Tasikmalaya through a descriptive qualitative approach for 18 weeks of implementation. The BASTE (Body, Action, Space, Time, Energy) method was used as a framework in exploring creative dance movements inspired by five types of Sundanese pakakas: se'eng, aseupan, hihid, korang, and koja (Kusuma & Hartono, 2023). The results of the study showed a significant increase in: (1) understanding of Sundanese pakakas from 25% to 85% (+60%), (2) exploration of creative movement from 20% to 90% (+70%), (3) character development from 30% to 88% (+58%), (4) motor skills from 40% to 92% (+52%), and (5) appreciation of local culture from 15% to 90% (+75%). The learning rubric assessment showed that 94% of students achieved the "Very Good" or "Good" category in all aspects of the assessment. The implications of this study indicate that the integration of dance with traditional pakakas is an effective medium in preserving local culture as well as developing the creativity and character competencies of elementary school students.